Pengembangan Kelas Virtual Interaktif Satu Lembar (KVISL) pada Materi Indahnya Mengampuni - Jenri Ambarita; Agusthina Siahaya (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This study aims to develop a One Sheet Interactive Virtual Classroom (KVISL) dan to obtain data onthe feasibility, practicality and effectiveness of KVISL. This research and development is based onthe lack of learning media for Christian religious education and the low creativity of teachers inmaking interesting learning media to support learning. This research is a type of RnD research withADDIE approach. Data obtained from development activities will be analyzed using a quantitativedescriptive approach. Data in the form of numbers will be converted into qualitative data using aLikert scale. The results of the research show that KVISL has been successfully developed with thestages of analysis, design, development, and implementation and evaluation. KVISL is declaredeligible for use based on the assessment of material experts with a final score of 4.7 (Very Eligible);while the media expert final score is 4.12 (adequate). Likewise, the small group trial obtained a finalscore of 4.72 (Very Eligible). And small group trials on students got a final score of 4.81 (VeryEligible). Based on the analysis of students' pretest and posttest results, it shows that KVISL is veryeffective and practical to use in learning.